Ready to read: how staff training impacts literacy skills in pre-schools - Karemaker, A; Jelley, F; Sylva, K; Kanji, G; Murphy, V (British Psychological Society, 2014)
Objectives: To determine whether a childcare staff-training intervention designed to improve practitioners’ language and literacy instruction can in turn build children’s language and literacy skills. The training was expected to assist practitioner’s efforts to support children in acquiring emergent literacy skills. Method: A quasi-experimental, pre- and post test comparison design was adopted. Four childcare centres received the staff-training (intervention group) and four centres were in the (waiting) comparison group. The intervention was delivered through four 2-hour sessions over a 4-week period. It focused on supporting staff to develop knowledge and skills for implementing effective emergent literacy activities. Seventy-one 3-4 year old children (Intervention: n=42; Comparison: n=29) were pre- and post tested on emergent literacy measures. Results: An ANCOVA revealed that the intervention children performed significantly better at post-test on the Naming Vocabulary measure. Conclusions: A four-week professional training programme for early years staff can successfully improve children’s emergent literacy skills.